Driving Miss Norma : one family's journey saying "yes" to living - Bauerschmidt, Tim; Liddle, Ramie (New York : HarperOne, an imprint of HarperCollinsPublishers, 2017)
"When Miss Norma was diagnosed with uterine cancer, she was advised to undergo surgery, radiation, and chemotherapy. But instead of confining herself to a hospital bed for what could be her last stay, Norma--newly widowed after nearly seven decades of marriage--rose to her full height of five feet and told her doctor, 'I'm ninety years old. I'm hitting the road.' Packing what she needed, Norma took off on an unforgettable cross-country journey with three professional nomads--her retired son Tim, his wife Ramie, and their standard poodle Ringo--in a thirty-six-foot RV."--
Keywords: Bauerschmidt, Norma, -- 1925-2016 -- Travel -- United States; Bauerschmidt, Tim -- Travel -- United States; Liddle, Ramie -- Travel -- United States; Terminally ill -- Biography; Mothers and sons; Families -- Travel -- United States; Recreational vehicles -- United States; Older women -- United States -- Biography; Cancer -- Patients -- United States -- Biography; Quality of life -- Philosophy; Travel -- Psychological aspects; United States -- Description and travel